Kshara Kalpana According to Rasatarangini: A Textual Review - Gadekar Shubham; Taviad Krushnkumar; Kalsariya Bharat (International Journal of Ayurveda and Pharma Research, 2025)
Kshara (alkaline preparation) is widely used in various formulations as well as in various pharmaceutical procedures internally as well as externally. It also has therapeutic and surgical efficacy and shows results even when used in small doses. Aim: The present work aims to collect and summarize the information regarding Kshara Kalpana from Rasatarangini. Material and methods: Critical review of Kshara from Rasatarangini in various aspects such as its synonyms, properties, action on Dosha, Kshara prescribed in various formulations, percentage of Kshara in the formulation, other herbs used in the formulation, dose, indications, Kshara prescribed in various pharmaceutical procedures, and its practical application. Results:  Rasatarangini describes 13 Kshara with Vata-Kaphaghna properties, Swarjikakshara having the most synonyms (16). They are vital in pharmaceutical processes, with usage varying from Trikshara (Yavakshara, Swarjikakshara, Tankana) at 16.6% each in Parada Shodhana to 25% Tankana in Abhraka Satvapatana. The text details 18 Kshara-containing formulations, such as Gandhakadya Malahara (0.43% Tankana) and Shrisiddha Hinguleshwara (50% Tankana). Additionally, 11 Kshara Aamayika Prayogas (practical applications) are noted, where Ksharas are combined with Bhasmas. Rasatarangini indicates these compounds for conditions like Gulma (abdominal lump) (11) and Drushta Vrana (infected wound) (7). Preparations use both traditional and modified methods, including Nimbukamliya Kshara. Typical doses are 2–12 Gunja (250 mg - 1.25 g), highlighting their significant role in Rasashastra. Conclusion: Kshara in Rasatarangini serves key therapeutic and pharmaceutical roles. This review gives to enrich existing knowledge and provide insights for researchers in this field of education and study.